Characteristics of Tuna Viscera (Thunnus sp.) Hydrolysate Protein Fermented by Bacillus licheniformis - Galih Nugroho; Arning Wilujeng Ekawati; Hartati Kartikaningsih (Research Journal of Life Science, 2020)
This study aims to analyze the nutritional composition of the degree of hydrolysis and amino acids in the internal organ waste of tuna and the protein hydrolyzate of tuna's internal organs after fermentation using the Bacillus licheniformis bacteria. The analysis showed that the protein content of tuna offal was 53.52%, and after fermentation by Bacillus licheniformis, bacteria were able to increase protein levels from 56.04. The degree of hydrolysis of protein (DH) showed an increase of 13.24% in tuna offal to 22.28% of protein hydrolyzates are fermented tuna innards. The total essential amino acids and non-essential amino acids in the fermented tuna innards' protein hydrolyzates increased during the fermentation process. The highest levels of essential amino acids were found in arginine as high as 3.632965 at the 96th hour, and the lowest histidine was 1.082602. In contrast, for the highest non-essential amino acids, there was glycine at 8.52223, and the lowest for tyrosine was 1.272592.